2008
DOI: 10.1183/09031936.00092908
|View full text |Cite
|
Sign up to set email alerts
|

Steroids augment relengthening of contracted airway smooth muscle: potential additional mechanism of benefit in asthma

Abstract: Breathing (especially deep breathing) antagonises development and persistence of airflow obstruction during bronchoconstrictor stimulation. Force fluctuations imposed on contracted airway smooth muscle (ASM) in vitro result in its relengthening, a phenomenon called force fluctuation-induced relengthening (FFIR). Because breathing imposes similar force fluctuations on contracted ASM within intact lungs, FFIR represents a likely mechanism by which breathing antagonises bronchoconstriction. While this bronchoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 47 publications
0
32
0
1
Order By: Relevance
“…This is exactly the angle that LAKSER et al [17] chose in the current issue of the European Respiratory Journal. Here one recognises a physiological approach.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…This is exactly the angle that LAKSER et al [17] chose in the current issue of the European Respiratory Journal. Here one recognises a physiological approach.…”
mentioning
confidence: 77%
“…This inactivates p38 MAPK, thereby enhancing the stretch of precontracted airway smooth muscle by periodic strain. The data show that [17], first, incubation of isotonicly shortened canine tracheal smooth muscle strips with dexamethasone prior to and during force fluctuations significantly augment muscle relengthening. Secondly, dexamethasone increases the expression of MKP-1 in cultured canine tracheal smooth muscle cells, which is accompanied by a decrease in phosphorylation of a downstream target of p38 MAPK, heat shock protein 27 [17].…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Second, the deformable pharyngeal airway duration inspiration and the active contraction of respiratory muscles during forced exhalation in an asthma attack could promote the collapse of the upper airway at night [21]. Third, corticosteroid therapy may affect the pharyngeal airway and render pharyngeal dilators more floppy, thus reducing their ability to protect the upper airway patency during sleep [22,23]. More clinical trials or animal studies should be performed to confirmed these mechanisms or pathophysiology.…”
Section: Discussionmentioning
confidence: 99%